Pengaruh Modal Psikologi Dan Person Job Fit (P-J Fit) Terhadap Kinerja Pegawai Dimediasi Komitmen Organisasional (Studi Pada Sekretariat Daerah Kabupaten Batang) - Prabowo, Imam; Soliha, Euis (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The aim of the research is to examine the influence of Psychological Capital, Person Job Fit (P-J Fit) on Employee Performance and Organizational Commitment as mediating variables at the Regional Secretariat of Batang Regency. The results of the analysis show that there is an insignificant influence of Psychological Capital on organizational commitment, and Person Job Fit has a significant influence on Organizational Commitment, with an Adjusted R-square value of 0.362, a significance value of 0.110 and 0.000. This shows that Psychological Capital and P-J Fit have a significant influence. For the second analysis, there is an influence of Psychological Capital, P-J Fit and Organizational Commitment on Employee Performance with an Adjusted R-square value of 0.541 with significance values ​​of 0.000 and 0.008 (significant) and 0.775 (not significant), respectively. This shows that Psychological Capital and P-J Fiti are significant to employee performance, while Organizational Commitment is not significant to employee performance. For the mediation test, the organizational commitment variable was unable to mediate the influence of Psychological Capital and P-J Fit on employee performance.